Konstruksi Sosial Media Terhadap Kekuatan Personal Branding Tri Risma Maharani dalam Proses Komunikasi Politik Kontemporer (Analisis Framing Pemberitaan Di Media Online Republika.co.id dan Tempo.com) - Misni Astuti (Jurnal Dakwah dan Komunikasi, 2016)
belongs to the people. In the process of democracy, there is a guarantee of political rights including for women's political rights. Risma Trimaharini presence is concrete evidence that women's leadership is qualified in public areas. This study aims to identify and describe how the power of personal branding in contemporary political communication process established by Risma as female political leaders, who proved to have a high elektabilitas in a political event in Surabaya, especially from the standpoint of research institution. This is a descriptive qualitative method Robert N. Entman framing by reviewing the online media report published by Tempo.co and Republika.co.id. The results of the study found was that both media construct and framing the figure Risma as a political woman figure who has a personal branding both in the public circumstances, with a friendly personality, discipline, and sensitive to the social reality around him, was able to make Risma increasingly admired, communication politics in the wake Risma rated on target and very humane, this is reflected by its proximity to the community at all levels.